The Cupcake Club - Berk, Sheryl (Peace, Love and cupcakes, 2012)
Fourth grader Kylie Carson starts a cupcake club as a way to make new friends at her new school, but it may be the end of the Cupcake Club when mean girl Meredith tries to sabotage Kylie and her fellow bakers' big cupcake party.